POTENSI PEMANFAATAN CO2 DAN HIDROGEN SEBAGAI BAHAN BAKAR ALTERNATIF DI INDONESIA - Tata Sutardi; Abdul Hamid Budiman (Jurnal Energi dan Lingkungan (Enerlink), 2020)
Indonesia has various types of energy sources, either from conventional energy sources or from newand renewable energy sources. Currently, Indonesia has a program to construct of 35 GW of coal-firedpower plant, as well as an intensive development of Geothermal power plant, since it's reserve isabundant. The construction of these types of power plants has a potency to increase Green House Gas(GHG) production, and therefore it necessarily needs to be anticipated. In 2018, there was 543 millionton of CO2 produced in Indonesia and about a half sourced from power generation sectors. Referring tothe ratio of 1 to 1.5 of CO2 converted with the process of hydrogenation, this indicates a promisingamount of methanol can be obtained. However, there are some challenges need to be overcome toachieve this beneficiary. This paper encloses a description of each challenge, with the main descriptionis on the potency of implementation in Indonesia. Some models from existing development aredescribed, to identify the process of development. This information can be used as a consideration forthe implementation in Indonesia.Keywords: CO2 utilization, Metanol formation, Hydrogen, Green House Gas, Geothermal power plant,Gas power plant